Pendekatan Blue Ocean Strategy pada Labuda Kopi dalam Menghadapi Persaingan Coffe Shop di Sidoarjo - Fajerul Dicky Saputra; Acep Samsudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the strategy used by managers to face competition in coffee shops in Sidoarjo using the Blue Ocean Strategy Approach. In this study, the method used was a qualitative descriptive approach. Qualitative descriptive research has the objective of describing, illustrating, and explaining in greater depth the problem being observed. In qualitative research, the main subject of research is human beings, and the results of this research are manifested in the form of words appropriate to the field situation. The results of this research through the E-R-R-C scheme set for Labuda Kopi are as follows: First, in the step to eliminate, the menu of Honey Spices Lime and Honey Spices Flower Tea is abolished. Then, in the subtract step, the price of the product that has been set will be reduced. Furthermore, in the step of upgrading, Labuda Kopi will add stands with shade, improve marketing strategies, and increase the facilities provided. Finally, in the creation step, Labuda Kopi will create new distinctive coffee variants and also create a new set menu.